Mengupas Mpasi Dini: Antara Tradisi, Pengetahuan, dan Risiko Stunting Balita di Desa Lembung Gunong Bangkalan - Hetti Mulyaningsih; Hoiriyeh Hoiriyeh; Aminah Dewi Rahmawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to understand the traditional practice  of early complementary feeding (MPASI) among toddlers in Lembung Gunong Village, Kokop District, Bangkalan Regency, as well as to explore the influence of tradition and mothers’ knowladge regarding this practice. This research employs a qualitative approach using a phenomenological analysis to reveal the social meanings behind the tradition of early complementary feeding. The data was collected through direct observations,in-depth interviews with key informants, documentation, and secondary sources to provide a well-rounded view of the  community’s experiences. The results show that early complementary feeding has become a common practice among mothers due to the strong influence of tradition and limited knowledge about the appropriate time for complementary feeding. Mothers tend to give solid food earlier because it is considered a customary practice that has been passed down from generation to generation. Applying social construction theory, the study explains how such habits are formed and socially accepted in the community. The study recommends enhanced nutritional education aimed at reducing early complementary feeding practices and thereby lowering the incidence of stunting in Lembung Gunong Village.